(untitled) (Praxis Educativa, 2025)
The present work seeks to share some contributions of the affective turn around the findings derived from the research within the framework of the thesis of Bachelor of Science in Education of the Argentine National University of the city of Mar del Plata, the same The objective was understand the processes of reconfiguration of emotional and professional ties in the academic life of students of the Bachelor of Education Sciences at the National University of Mar del Plata in the period 2019 -2022, based on an autoethnographic study that privileges conversation and horizontality as significant methodologies, where reciprocity represents a responsibility that advocates a “reciprocal practice.”